Using Longitudinal Self-Report Data to Study the Age-Crime Relationship - Kim, Jaeok (Journal of quantitative criminology, 2018)
Given the growing reliance on longitudinal self-report data for making causal inferences about crime, it is essential to investigate whether the within-individual change in criminal involvement exists and is not a measurement artifact driven by attrition or survey fatigue—a very real possibility first identified by Lauritsen (Soc Forces 77(1):127-154, 1998) using the National Youth Survey (NYS). The current study examines whether the same threats to the validity of within-individual change in criminal involvement exist in the National Longitudinal Survey of Youth 1997 cohort (NLSY97).